Effect of the Size of the Left Atriumo Sustained Sinus Rhythm in Patients Undergoing Mitral Valve Surgery and Concomitant Bipolar Radiofrequency Ablation for Atrial Fibrillation - Harun Avdagić; Selma Sijerčić Avdagić; Melika Pirić Avdagić; Miha Antonič (Acta Clinica Croatica, 2017)
Atrial fibrillation is associated with systemic embolization and complications due to anticoagulant therapy. Radiofrequency ablation has been established as an effective and safe method for the treatment of atrial fibrillation. The aim of this study was to evaluate the effect of the size of the left atrium on the outcome of surgical radiofrequency ablation. Forty patients scheduled for elective mitral valve surgery and radiofrequency ablation were enrolled in the study. Group 1 consisted of patients with a left atrium diameter ≤5 cm and group 2 of patients with left atrium diameter >5 cm. The primary endpoint of the study was stable sinus rhythm 6 months postoperatively. At 6 months postoperatively, sinus rhythm was present in significantly more group 1 patients as compared with group 2 patients, i.e. 15 (75%) vs. 8 (40%), p=0.025. Multivariate analysis proved the size of the left atrium to be an independent predictor of the radiofrequency ablation outcome. Accordingly, the size of the left atrium was demonstrated to be an important predictor of the outcome of radiofrequency ablation for atrial fibrillation. A lower cut-off value of surgical reduction of the atria than previously reported should be considered in order to improve the radiofrequency ablation outcome.